Brief descriptive study of the environmental phenomenon in its two dimensions: Environmental damage and ecological damage (2017)
Introduction: this article presents a descriptive study on the treatment of environmental damage in its double legal assessment, based on the general theory of damage. It includes some relevant jurisprudence and case law trends in recent times, in order to inquire whether the transposition of classic damage is sufficient to understand environmental damage and ecological damage, taking into account its features and the characters of environmental damage. Methodology: the descriptive approach and the deductive method were applied to study the environmental phenomenon from its two conceptual dimensions: environmental damage and ecological damage, which respond to realities, effects and liabilities that are appreciated differently. These aspects should be assessed holistically in order to establish a clear vision of difference and similarity factors, with their consequent involvement in responsibility. Results: conceptions of environmental damage and ecological damage, from the legal point of view, cannot be treated as equivalent meanings, since difference factors have been established from jurisprudence and case law, finding that the natural environment represents the difference factor  between classic damage and environmental damage, while similarity is given by the effect on the personal, equity and moral spheres they connote. Conclusions: in order to attain a correct meaning of environmental damage, it is necessary to detach it from its equity implication and avoid establishing priority categories of environmental damage over ecological damage.